Retracted: A multicentre randomised controlled trial of the effect of intra‐operative dexmedetomidine on cognitive decline after surgery. (5th March 2019) - Cheng, X.‐Q.; Mei, B.; Zuo, Y.‐M.; Wu, H.; Peng, X.‐H.; Zhao, Q.; Liu, X.‐S.; Gu, E.; ,
Summary: Peri‐operative dexmedetomidine can reduce rates of delirium immediately after surgery. We aimed to assess the effect of dexmedetomidine on cognition up to six postoperative months and its association with changes in serum concentrations of brain‐derived neurotrophic factor on the third and seventh postoperative days. We randomly allocated 535 patients aged 65 years or more undergoing scheduled gastro‐intestinal laparotomy to: intra‐operative dexmedetomidine, 0.5 μg.kg −1 bolus followed by 0.4 μg.kg −1 .hr −1 infusion (n = 269), or placebo (n = 266). Dexmedetomidine reduced the rate of cognitive impairment: on the third postoperative day, 40/269 vs. 65/266, p = 0.006; on the seventh postoperative day, 31/269 vs. 49/266, p = 0.03 and at one postoperative month, 42/250 vs. 61/248, p = 0.04. Cognitive impairment at seven postoperative days was associated with changes in brain‐derived neurotrophic factor concentrations on the third and seventh postoperative days; area under the receiver operating characteristic curve 0.63, p < 0.001 and 0.58, p = 0.016, respectively. Intra‐operative dexmedetomidine reduced cognitive decline up to one postoperative month in elderly patients undergoing scheduled laparotomy, which was associated with changes in serum brain‐derived neurotrophic factor.